Pembuatan Media Pembelajaran Berbasis Virtual Assistant Pictory & Fliki AI (Artificial Intelligence) Di SMP Negeri 6 Kota Gorontalo - Nuramila Nuramila; Ayu Hidayanti Ali; Puspita Dian Agustin; Dakia N Djou; Eka Sartika (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
Currently, technological developments are increasingly rapid. There are new advances in human life, one of which is artificial intelligence or AI (Artificial Intelligence), which is a computer system created in such a way as to be able to interact with the world around it through intelligent behavior like humans. Artificial Intelligence can target various domains, including the education sector. The role of teachers will be greatly transformed by artificial intelligence, including in terms of creating learning media. Media in this case is very necessary to attract students' enthusiasm in participating in learning, as well as to create fun, meaningful, creative and interactive learning. The use of Pictory and Fliki AI makes it easier for teachers to create learning media because the Pictory and Fliki features are able to automatically visualize a text into an educational video according to a certain topic. The targets of activities in implementing this service activity are teachers at SMP Negeri 6 Gorontalo City. This activity contributes to the creation of creative and fun learning based on current developments, namely the use of technology. The implementation of this service activity uses the Training and Mentoring method.